Eufemism and dyphemisms in the comments column youtube serambinews - Nisak, Khairatin; Harun, Moh; Iskandar, Denni; Yusuf, Yusri; Arianto, Budi; Ramli, Ramli (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The objective of this research is to enhance readers' understanding and proficiency in using euphemisms and dyphemisms effectively and employing language skillfully in communication. The employed methodology is a descriptive research method characterized by a qualitative approach. The data for this research consists of comments that include euphemisms and dysphemisms. The source of the data is the comments section of Serambinews YouTube, contributed by netizens. The research analyzed a total of 105 data points, comprising 34 instances of euphemism data and 71 instances of dysphemism data. The data analysis process for this research entails data selection, data classification, data analysis, and the formulation of conclusions. The research findings indicate that the utilization of euphemisms and dysphemisms is influenced by the underlying context. Euphemisms are typically employed to convey a more pleasant or inoffensive tone, while dysphemisms serve to ridicule, inquire, comment disapprovingly, express anger, reiterate a request, assign blame, respond to criticism, or make jokes.